2007
DOI: 10.1021/ja071122v
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Nanocomposites of Metals, Metal Oxides, and Carbon Nanotubes via Self-Assembly

Abstract: Carbon nanotubes (CNTs)-based composites have attracted significant research interest in recent years, owing to their important applications in various technological fields. In this investigation, we describe a general approach to make CNTs-based nanocomposites via self-assembly. The method allows one to prepare binary composites as well as complex systems such as ternary or even quaternary composites where nanoparticles of active phases (e.g., metals and metal oxides) are used as primary building blocks. Six … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
250
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 361 publications
(264 citation statements)
references
References 79 publications
14
250
0
Order By: Relevance
“…[1][2][3] For instance, the synthesis and fabrication of inorganic nanotubes of, for example, MoS 2 , WS 2 , MoO 3 , V 2 O 5 , TiO 2 , ZrO 2 , Co 3 O 4 , ZnO, and GaN have advanced rapidly. [4][5][6][7][8][9][10][11] Furthermore, it has been found that self-assembled peptides can also build into tubular structures by means of hydrogen bonding, and give rise to a new class of supramolecular nanotubes. [12][13][14][15] Herein we report another type of supramolecular architecture, where Au(I) cations and alkanethiolate ligands are coordinated into thin platelet forms that then evolve into an open tubular configuration.…”
mentioning
confidence: 99%
“…[1][2][3] For instance, the synthesis and fabrication of inorganic nanotubes of, for example, MoS 2 , WS 2 , MoO 3 , V 2 O 5 , TiO 2 , ZrO 2 , Co 3 O 4 , ZnO, and GaN have advanced rapidly. [4][5][6][7][8][9][10][11] Furthermore, it has been found that self-assembled peptides can also build into tubular structures by means of hydrogen bonding, and give rise to a new class of supramolecular nanotubes. [12][13][14][15] Herein we report another type of supramolecular architecture, where Au(I) cations and alkanethiolate ligands are coordinated into thin platelet forms that then evolve into an open tubular configuration.…”
mentioning
confidence: 99%
“…e small positive displacement observed in this work suggests that an electronic interaction between TiO 2 and the MWCNT substrate was established [37], resulting from a close interaction between the nanotubes and the oxide coating. Advances in Materials Science and Engineering MWCNT sample.…”
Section: X-ray Photoelectron Spectroscopymentioning
confidence: 65%
“…e other two peaks with binding energies of 531.7 and 532.9 eV are assigned to the O-H and C O groups, respectively. Similarly to the Ti 2p spectrum, the main peak in O 1s is slightly displaced (0.9 eV), as a result of the interaction and consequent surface charge transfer between TiO 2 and MWCNTs [37]. e C 1s spectrum was adjusted to four peaks, representing the C C binding energy of MWCNTs of 284.7 eV, as well as C-O, C O, and COOenergies of 286.1, 287.9, and 290.1 eV, respectively.…”
Section: X-ray Photoelectron Spectroscopymentioning
confidence: 94%
“…[1][2][3][4][5] The alternating pulses of metal precursor and oxygen source, as well as the self-limiting character of the reaction, enable uniform coating of surfaces with extremely high aspect ratios. Increasing the number of deposition cycles, the conformity of the metal film increases.…”
Section: Introductionmentioning
confidence: 99%